Factors associated with lift equipment use during patient lifts and transfers by hospital nurses and nursing care assistants: A prospective observational cohort study. (March 2019) - Kucera, Kristen L.; Schoenfisch, Ashley L.; McIlvaine, Jennifer; Becherer, Lori; James, Tamara; Yeung, Yeu-Li; Avent, Susan; Lipscomb, Hester J.
Abstract: Background: Despite wide availability of patient lift equipment in hospitals to promote worker and patient safety, nursing staff do not consistently use equipment. Objective: To determine the influence of factors on the use or non-use of lift equipment during patient lifts/transfers. Design: Prospective observational cohort study. Setting: One university teaching hospital and two community hospitals in a large health system in southeastern United States. Participants: 77 nurses and nursing care assistants with patient handling duties in critical care, step-down and intermediate care units. Methods: Participants recorded information about all patient lifts/transfers during their shifts during a 1 week period per month for three months: type of lift/transfer, equipment use, type of equipment, and presence of 20 factors at the time of the lift/transfer. With the patient lift/transfer as the unit of analysis, the association (risk ratios (RR) and 95% confidence intervals (CI)) between factors and equipment use was examined using multivariate Poisson regression with generalized estimating equations. Results: Seventy-seven participants (465 person-shifts) reported 3246 patient lifts/transfers. Frequent lifts/transfers included bed-to-toilet (21%), toilet-to-bed (18%), bed-to-chair (13%), chair-to-bed (13%), chair-to-toilet (6%), and toilet-to-chair (6%). Equipment was used for 21% of lifts/transfers including powered floor based dependent lift (41%), powered sit-to-stand lift (29%), non-powered sit-to-stand lift (17%), air-assisted lateral transfer device (6%), ceiling lift (3%), and air-assist patient lift (3%). Factors associated with equipment use included: availability of equipment supplies (RR = 9.61 [95%CI: 6.32, 14.63]), staff availability to help with equipment (6.64 [4.36, 10.12]), staff preference to use equipment (3.46 [2.48, 4.83]), equipment required for patient condition (2.38 [1.74, 3.25]), patient inability to help with lift/transfer (2.38 [1.71, 3.31]), equipment located in/by patient room (1.82 [1.08, 3.06]), sling already under patient (1.79 [1.27, 2.51]), and patient size/weight (1.38 [0.98, 1.95]). Lower patient mobility score (3.39 [2.19, 5.26]) and presence of physical or mental impairments (2.00 [1.40, 2.86]) were also associated with lift equipment use. Factors associated with non-use of equipment included: patient/family preference (0.31 [0.12, 0.80]), staff assisting with lift did not want to use equipment 0.34 ([0.17, 0.68]), patient condition (0.48 [0.20, 1.20]), and patient almost fell (0.66 [0.45, 0.97]). Conclusions: Patient, worker, equipment, and situational factors influence whether nursing staff used equipment to lift/transfer a patient. Quantifying and understanding these factors associated with lift equipment use and non-use provides specific information for hospitals and safety professionals to enhance effectiveness of future organizational and ergonomic intervention efforts to prevent work-related patient-handling injuries.